The Effect of an HIV Self-Management Intervention on Neurocognitive Behavioral Processing. (July 2019) - Webel, Allison R.; Schreiner, Nathaniel; Salata, Robert A.; Friedman, Jared; Jack, Anthony I.; Sattar, Abdus; Fresco, David M.; Rodriguez, Margaret; Moore, Shirley
People living with HIV (PLHIV) are increasingly diagnosed with comorbidities which require increasing self-management. We examined the effect of a self-management intervention on neurocognitive behavioral processing. Twenty-nine PLHIV completed a two-group, 3-month randomized clinical trial testing a self-management intervention to improve physical activity and dietary intake. At baseline and 3 months later, everyone completed validated assessments of physical, diet, and neurocognitive processing (functional magnetic resonance imaging [fMRI]–derived network analyses). We used linear mixed effects modeling with a random intercept to examine the effect of the intervention. The intervention improved healthy eating ( p = .08) but did not improve other self-management behaviors. There was a significant effect of the intervention on several aspects of neurocognitive processing including in the task positive network (TPN) differentiation ( p = .047) and an increase in the default mode network (DMN) differentiation ( p = .10). Self-management interventions may influence neurocognitive processing in PLHIV, but those changes were not associated with positive changes in self-management behavior.